Chapter Attorno alle nominalizzazioni - Kreisberg, Alina (Biblioteca di Studi Slavistici, 2016)
The paper deals with the problem of the particular kind of verbal nominalization occuring in Polish. Such formations are similar to the English gerunds in -ing and are defined in the Polish linguistic tradition as categorial. The purpose of the article is to examine whether their categorial status should be regarded as a purely formal or semantic also.